(untitled) (International journal of medical sciences, 2026)
The menopausal transition is associated with profound endocrine and metabolic changes that increase susceptibility to metabolic syndrome. Although estrogen deficiency is a major contributing factor, accumulating evidence indicates that genetic predisposition plays a decisive role in determining metabolic adaptability in menopausal women. This article synthesizes contemporary findings on genetic determinants involved in the development of metabolic syndrome during menopause. Particular attention is given to genes regulating insulin signaling, adipokine secretion, lipid metabolism, inflammatory responses, oxidative stress, and mitochondrial function. The interaction between genetic background, hormonal decline, and environmental influences is analyzed as a key mechanism underlying metabolic maladaptation. Recognition of genetic susceptibility patterns may facilitate early identification of high-risk individuals and support the development of personalized preventive and therapeutic strategies in menopausal healthcare.